ANALISIS KEPUASAN MASYARAKAT ATAS KUALITAS PELAYANAN PADA KANTOR KECAMATAN LAWEYAN DI SURAKARTA - Anisa Dwi Yulianti, Eny Kustiyah & Istiqomah (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
This study aim to determine whether physical evidence, reliability, responsiveness, assurance, and empathy affect simultaneously and partially to the satisfaction of community at district office Laweyan Surakarta. The population in this study is the community of service users at the district office Laweyan Surakarta amounted to 66,484 people and took a sample of 100 respondents. Data analysis techniques used were instrument test, classical assumption test, and hypothesis test. Simultaneously the physical evidence, reliability, responsiveness, assurance, and empathy have positive and significant impact on the satisfaction of the community at the district office of Laweyan Surakarta. Partially, physical evidence doesn’t have significant influence on satisfaction of community at the Laweyan sub-district office in Surakarta, the reliability doesn’t have significant effect on satisfaction of community at the Laweyan sub-district office in Surakarta, the responsiveness has significant effect the community satisfaction at the Laweyan Surakarta sub-district office, has significant influence on satisfaction of community at the Laweyan sub-district office in Surakarta, empathy has significant effect on the satisfaction of community at Laweyan sub-district office in Surakarta. Keywords: service quality, community satisfaction.